The Impact of Business Analytics on Education Sectors-A Study - V. , Nalini; M. , Bagirathi (International Journal of Psychosocial Rehabilitation, 2020)
Business analytics is believed to be an enormous boon for organizations, as well as in emerging education sectors. Since it helps offer timely insights over the competition, helps optimize business processes, and helps generate growth and innovation opportunities. As organizations start their business analytics initiatives, many strategic questions, just like the thanks to operationalize business analytics so on drive the foremost value, arise. Recent Information Systems (IS) literature has focused on explaining the role of business analytics and thus the necessity for business analytics. However, little or no attention has been paid to understanding the theoretical and practical success factors related to the operationalization of business analytics. The primary objective of this study is to fill that gap within the IS literature by empirically examining business analytics success factors and exploring the impact of business analytics on education sectors. Through a qualitative study, we gained deep insights into the success factors and consequences of business analytics. Our research informs and helps shape possible theoretical implementations of business analytics.